Participation of pregnant women in a community-based nutrition program in Mumbai's informal settlements: Effect on exclusive breastfeeding practices - Chanani, Sheila (PLoS One, 2018)
BACKGROUND: In urban Maharashtra, India, approximately half of mothers exclusively breastfeed. For children residing in informal settlements of Mumbai, this study examines factors associated with exclusive breastfeeding, and whether exclusive breastfeeding, in a community-based nutrition program to prevent and treat wasting among children under age three, is associated with enrolment during the mother’s pregnancy. METHODS: The nutrition program conducted a cross-sectional endline survey (October-December 2015) of caregivers in intervention areas. Factors associated with exclusive breastfeeding for infants under six months of age were explored using multi-level logistic regressions. Additionally, program surveillance data collected during home-based counselling visits documented breastfeeding practices for children under six months of age. Using the surveillance data (January 2014-March 2016), exclusive breastfeeding status was regressed adjusting for child, maternal and socioeconomic characteristics, and whether the child was enrolled in the program in utero or after birth. RESULTS: The community-based endline survey included 888 mothers of infants. Mothers who received the nutrition program home visits or attended group counselling sessions were more likely to exclusively breastfeed (adjusted odds ratio 1.67, 95% CI 1.16, 2.41). Having a normal weight-for-height z-score (adjusted odds ratio 1.57, 95% CI 1.00, 2.45) was associated positively with exclusive breastfeeding. As expected, being an older infant aged three to five months (adjusted odds ratio 0.34, 95% CI 0.25, 0.48) and receiving a prelacteal feed after birth (adjusted odds ratio 0.57, 95% CI 0.41, 0.80) were associated with lower odds of exclusively breastfeeding. Surveillance data (N = 3420) indicate that infants enrolled in utero have significantly higher odds of being exclusively breastfed (adjusted odds ratio 1.55, 95% CI 1.30, 1.84) than infants enrolled after birth. CONCLUSIONS: Prenatal enrolment in community-based programs working on child nutrition in urban informal settlements of India can improve exclusive breastfeeding practices.